Isolated bilateral hypoglossal nerve paralysis following an atlanto-occipital dislocation: A case report - Mano, Tomoo; Tatsumi, Saori; Fujimura, Shigekazu; Hotta, Naoki; Kido, Akira (Frontiers in Neurology, 2022)
The present report highlights a case of successful treatment of an 11-year-old male patient who presented with an atlanto-occipital dislocation and multiple fractures of the forearm, pelvis, and lower leg because of a fall. The patient experienced dysarthria and paralysis of the tongue, which became completely immobile and could not be moved from side to side, impeding speech. The patient also experienced dysphagia due to the inability to propel food toward the pharynx and chewing attempts resulted in scattering of food residue throughout the oral cavity. The lack of tongue mobility led to saliva accumulation, forcing the patient to swallow frequently, which was possible as larynx movement was unaffected. The other cranial and motor sensory nerves appeared normal. Our diagnostic examinations confirmed the presence of isolated bilateral paralysis of the hypoglossal nerve secondary to traction at the base of the skull. The patient remained unable to prostrate his tongue and tongue slowly atrophied 2 weeks after admission. Electromyography revealed denervation of the tongue and minimal active contraction of the single motor units. The immobilization therapy and rehabilitation therapy were initiated to improve tongue movement, but this was unsuccessful and 1 month after the accident, the patient’s tongue remained to be atrophied. The patient was placed on a soft food diet and experienced no difficulty in swallowing either saliva or food 3 months after admission. Tongue mobility was deemed normal. Electromyography 6 months after the initial episode revealed normal motor unit potentials during contractions. We postulate that compression and stretching of the bilateral hypoglossal nerves against the greater horn of the hyoid bone was a probable cause of the hypoglossal palsy. Using the immobilization and rehabilitation therapy likely supported the recovery of function and resulted in a good prognosis.